2004
DOI: 10.1007/s10295-004-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of biopesticide production processes using wastewater sludge as a raw material

Abstract: Studies were conducted on the production of Bacillus thuringiensis (Bt)-based biopesticides to ascertain the performance of the process in shake flasks, and in two geometrically similar fermentors (15 and 150 l) utilizing wastewater sludge as a raw material. The results showed that it was possible to achieve better oxygen transfer in the larger capacity fermentor. Viable cell counts increased by 38-55% in the bioreactor compared to shake flasks. As for spore counts, an increase of 25% was observed when changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In the case of both raw and pre-treated sludges, K L a, OTR and OUR increased in the beginning of the fermentation, attained a peak towards the end of exponential growth, then decreased followed by a tendency to become constant during the rest of the fermentation. A similar trend was also observed during Bt fermentation of non-treated sludge in bench and pilot scales fermentation (Yezza et al 2004a). Maximum K L a values were higher in pre-treated sludge (192.9 and 157.6 h )1 in thermo-alkaline and oxidative treatment, respectively) than in raw sludge (117.2 h )1 ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the case of both raw and pre-treated sludges, K L a, OTR and OUR increased in the beginning of the fermentation, attained a peak towards the end of exponential growth, then decreased followed by a tendency to become constant during the rest of the fermentation. A similar trend was also observed during Bt fermentation of non-treated sludge in bench and pilot scales fermentation (Yezza et al 2004a). Maximum K L a values were higher in pre-treated sludge (192.9 and 157.6 h )1 in thermo-alkaline and oxidative treatment, respectively) than in raw sludge (117.2 h )1 ).…”
Section: Resultssupporting
confidence: 80%
“…However, Tx values observed by LeBlanc (2004) were lower than the values recorded in this study. This was due to better oxygen transfer in fermentor compared to experiments performed in shake flasks (Yezza et al 2004a). Moreover, LeBlanc (2004) hydrolysed the sludge in a microwave oven without any agitation.…”
Section: Enhancement Of Entomotoxicity Potency In Thermo-alkaline Prementioning
confidence: 94%
“…The cost can be reduced by strain improvement, medium composition optimization by statistical methods, using alternative inexpensive substrates, or through the bioreactor operation and design [2,3,8,20]. Recently, the use of shake flask in reduction of the process cost and time, operational facilitation, and determination of optimum condition in cultivation, and then scaling up of bioreactor has been taken into consideration [21,22]. Several parameters including volumetric oxygen transfer coefficient, power input, agitation rate, superficial gas velocity, impeller tip speed, and Reynolds (Re) number are investigated as scale up criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in our laboratory has shown that wastewater sludge contains the necessary nutritional elements to sustain growth, sporulation and crystal formation by Bacillus thuringiensis (Lachhab et al 2001;Vidyarthi et al 2002;Yezza et al 2004Yezza et al , 2005. However, in such complex media, the presence of nutrient is not always enough to obtain good entomocidal activity (Tirado-Montiel et al 2001).…”
Section: Introductionmentioning
confidence: 97%